Developing Professional Communication Skills In Future Teachers Of Russian As A Foreign Language Within The Framework Of Higher Pedagogical Education (Eurasian Journal of Learning and Academic Teaching, 2026)
This article examines the development of professional and communicative competence in future Russian as a foreign language teachers in the context of the modernization of higher pedagogical education. The theoretical and methodological foundations of communication training are analyzed. The need to integrate linguistic, methodological, and intercultural components in the professional development of Russian as a foreign language teacher is substantiated